Measuring the Impact of Community-Driven Development Projects on Gender : A Toolkit for the Poverty Reduction Fund, Lao PDR - World Bank (World Bank, Washington, DC, 2017)
Community-driven development (CDD) projects seek to empower communities, reduce poverty, and improve economic and social conditions of the poor, typically in rural and remote areas. No less important, CDD also typically addresses two persistent gender gaps: (1) women's lack of voice in public decision making, and (2) their poor access to services and markets. Much of the development community finds CDD to be appealing, and its use is widespread and growing. Nonetheless, the evidence to support the assumption that CDD effectively promotes development and enhances women's opportunities can be strengthened. Although most development projects have monitoring systems, these systems often focus more on outputs and less on outcomes and impacts. Such systems do not provide policymakers, managers, and stakeholders with an understanding of the success or failure of their projects or whether the well-being of the intended beneficiaries has improved.